Development Of Historical Films In Modern Karakalpak Cinema - Tajadinova, Guljakhan (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article discusses the development of historical films in modern Karakalpak cinema and issues that need to be addressed in the future. One of the pressing issues in Karakalpak cinema is the creation of historical films for children based on the childhood lives of great people.